Tra i libri di Isacco Argiro - Gioffreda, Anna (Transmissions, 2020)
This book reconstructs the figure of Isaac Argyrus, a byzantine scholar active in Constantinople of the 14th century, with due regards to the context of his work. The paleographical and codicological analysis of his book collection forms the basis for the considerations on the role he played as both a copyist in the transmission of classical works and an author in the contemporary hesychast controversy.